Case Report: Tumor lysis syndrome in advanced, massive hepatocellular carcinoma with main portal vein invasion following atezolizumab plus bevacizumab therapy - Chou, Tien-Shin; Wu, Chun-Feng; Lin, Chih-Lang; Hsu, Chao-Wei (Frontiers in Oncology, 2025)
BackgroundTumor lysis syndrome (TLS) is extraordinarily rare in solid tumors. However, the combination of atezolizumab and bevacizumab (AB) in advanced hepatocellular carcinoma (HCC) has raised concerns for abrupt metabolic derangements. We describe a fatal episode of TLS precipitated by AB in HCC with main portal vein (Vp4) invasion, highlighting the need for vigilant risk stratification and early biochemical surveillance for high-tumor-burden disease.Case presentationA 65-year-old man with chronic hepatitis B and massive HCC (Vp4 invasion) had relatively preserved organ function at baseline. Two days after initiating atezolizumab (1,200 mg) and bevacizumab (15 mg/kg), he developed fever (38.5°C) and tachycardia (heart rate 112 beats/min [bpm]), rapidly progressing to circulatory shock on day 3. Laboratory workup revealed hyperuricemia (12.4 mg/dL), hyperphosphatemia (12.9 mg/dL), hyperkalemia (6.8 mmol/L), hypocalcemia (7.7 mg/dL), and acute kidney injury, meeting the Cairo–Bishop criteria for TLS. Imaging demonstrated abrupt cystic changes of the hepatic mass, suggesting rapid tumor necrosis. Despite aggressive fluid resuscitation and the initiation of hemodialysis, the patient succumbed to multiorgan failure within eight days after initiating AB.ConclusionThis case underscores that advanced HCC with extensive vascular invasion is at risk of severe TLS shortly after potent immuno-antiangiogenic therapy. Clinicians should incorporate thorough baseline risk assessments, prompt laboratory monitoring, and timely intervention into standard care algorithms for high-risk HCC. The rapid metabolic collapse observed here serves as a reminder that while combination therapy holds promise for improving survival in advanced HCC, it can also lead to life-threatening complications in specific subgroups. Careful selection of therapeutic options and shared decision-making with patients are critical to balancing potential benefits against severe adverse events, such as TLS.